PROSPECTS AND LIMITATIONS OF DAIRYING IN GUJRANWALA DISTRICT (PUNJAB -PAKISTAN) - Arif; M.; A. Iqbal; M. Younas; B. B. Khan; M. Sarwar; S. Ahmad (Journal of Animal and Plant Sciences, 2013)
A study involving survey of 120 respondents of different categories from district Gujranwala (Punjab-Pakistan) was conducted to investigate the trends in dairying Average milk production of cows and buffaloes was found to be 4.50 and 6.53 lit./day respectively. Milk is mostly (98.3 %) consumed as fresh processed and marketed to milk collectors in raw form. Combined animal feeding was the common practice with no special dietary allowance for high yielders. Average green fodder offered to lactating cows and buffaloes was found to be 43.49 ±2.67 and 59.03 ±1.39 kg/head/day, whereas corresponding values for dry cows and buffaloes were 26.46 ±2.13 and 39.48 ±1.58 kg/day, respectively. Lactating animals were preferred for concentrate feeding. Animals were vaccinated mainly against foot and mouth disease (FMD) and haemorrhagic septicaemia (HS). Adoption level of disinfection of the navel cord, dehorning (in cows), natural breeding, teat dipping, washing of udder and culling was 8.3, 25.8, 51.7, 20.8, 74 and 61.70 % respectively. Special feeding of dairy animals before calving was also reported by 41.7 % respondents. Record keeping was utterly lacking (91.7 %). Age at first breeding, age at first calving, lactation length, dry period, intercalving interval and productive life in case of buffaloes was 40.87±0.43, 52.48±0.48, 10.66±0.085, 4.35±0.051, 15.13±0.18 months and 9.22 ± 0.18 years respectively while in case of cattle the corresponding values were 29.11±1.280, 43.20±6.33, 9.12±0.37, 2.56±0.11, 12.50±0.50 months and 8.36 ±0.42 years, respectively. It may be inferred from these results that adoption of modern husbandry practices is still grossly lacking with a variable degree leading to low productivity and low profitability of the producer.
Keywords: Dairying; Punjab; Pakistan